2020
DOI: 10.1016/j.outlook.2020.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Registered nurse perceptions of factors contributing to the inconsistent brand image of the nursing profession

Abstract: Highlights An outdated brand image projects nurses as lacking in influence and autonomy. Nurses could use branding principles to develop and promote their desired image. Branding is most effective when members agree on a set of shared values. A strong brand message is built on “consistency of message and action over time.” Research is needed which could inform an accurate brand image for nursing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
81
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(82 citation statements)
references
References 38 publications
0
81
0
1
Order By: Relevance
“…Neste sentido, a educação continuada se afigura como um modelo inovador que trabalha com foco a transformar a realidade, contribuindo na busca do ensino-aprendizagem amplo, partindo do cotidiano do profissional de saúde e dar continuidade ao processo ensino-serviço (Godsey, Houghton, Hayes, 2020). Os resultados deste estudo se assemelham aos achados supracitados, uma vez que, o percurso acadêmico dos profissionais de saúde é parte da sua formação profissional, desse modo, a educação continuada em serviços proporcionaria a capacitação e continuidade na formação desses profissionais.…”
Section: Discussionunclassified
“…Neste sentido, a educação continuada se afigura como um modelo inovador que trabalha com foco a transformar a realidade, contribuindo na busca do ensino-aprendizagem amplo, partindo do cotidiano do profissional de saúde e dar continuidade ao processo ensino-serviço (Godsey, Houghton, Hayes, 2020). Os resultados deste estudo se assemelham aos achados supracitados, uma vez que, o percurso acadêmico dos profissionais de saúde é parte da sua formação profissional, desse modo, a educação continuada em serviços proporcionaria a capacitação e continuidade na formação desses profissionais.…”
Section: Discussionunclassified
“…8,9 A recent article revealed that some leaders contribute to the negative brand and image of nursing when they lack leadership development, did not have role models, and did not advocate for themselves. 10 However, in an earlier article, researchers reported that Generation Y nurses were cautious yet optimistic about their future leadership roles and the future of nursing. 11 Thus, midlevel and senior nurse leaders are in a unique position to model behaviors to foster and sustain professional identity in nursing.…”
Section: Key Pointsmentioning
confidence: 99%
“…16 The increasing complexity of practice environments calls for ongoing intellectual stimulation, new educational tools, and assets such as clinical reasoning and educational preparation to enable optimal collaboration to improve patient care outcomes. 2,10,20 Practice environments need to be conducive and stimulating for learning by modeling best practices. In that way, nurses can replicate these practices in future leadership roles or seek environments to practice that enhance their professional identity.…”
Section: Modeling Of Foster Professional Identity In Nursingmentioning
confidence: 99%
See 2 more Smart Citations